Pengaruh Metode dan Dosis Aplikasi Vermikompos Terhadap Pertumbuhan dan Hasil Tanaman Tomat (Lycopersicum esculentum Miil) Hidroganik - Ahmad Filardi; D Djuhari; N Nurhidayati (Universitas Islam Malang, 2021)
The soilless culture system now developed rapidly in line with the decrease of the area ofproductive farmland as well as to meet healthy food needs and nutritious high. Thisresearch developed a soilles culture by using vermicompost organic fertilizers.This studyaimed to test influence of application methods and doses vermicompost on the growthand yield of tomato grown in hidroganic system. This experiment used a FactorialRandomized Block Design. The first factor : application methods of vermicompostconsisting of three levels namely M1 = solid vermicompost, M2 = combination of solid andliquid vermicompost, M3 = liquid vermicompost. The second factor : doses ofvermicompost consisting of five levels namely V1 = 150 grams, V2 = 300 grams , V3 = 450grams , V4 = 600 grams and V5 = 750 grams per polibag, plus control treatment usinginorganic fertilizer. The research results showed that interaction between applicationmethods and vermicompost doses had a significant effect on the growth and yield oftomato plants. The best combination of treatment was solid vermicompost at a dose of600 g/polybag gave a growth of plant height of 78.50 cm, leaf number of 205.33, leaf area of 4516.75 cm2 and flower number 24.78. This treatment had the best yield parametersby the fruit number of 24,33, fruit set of 98,20% and total weight of fruit 447,22 g/plant.Based on the regresion analysis showed that the optimum dose of vermicompost for solidvermicompost was 709.50 g/plant and the maximum yield was 494.70 g/plant. This resultsuggests that the solid vermicompost application can be recommended for hidroganicculture of tomato.